2014
DOI: 10.1016/j.apenergy.2014.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer and thermodynamic performance of a parabolic trough receiver with centrally placed perforated plate inserts

Abstract: In this paper, a numerical investigation of thermal and thermodynamic performance of a receiver for a parabolic trough solar collector with perforated plate inserts is presented. The analysis was carried out for different perforated plate geometrical parameters including dimensionless plate orientation angle, the dimensionless plate spacing, and the dimensionless plate diameter. The Reynolds number varies in the range 1.02×10 4 ≤ Re ≤ 7.38 × 10 5 depending on the heat transfer fluid temperature. The fluid temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(57 citation statements)
references
References 30 publications
1
53
0
2
Order By: Relevance
“…Good agreement was achieved for heat transfer fluid temperature gain (ΔT) and collector thermal efficiency as shown in Table 2 and also in one of our previous investigations (Mwesigye et al, 2014a). …”
Section: Validation Of Numerical Modelsmentioning
confidence: 51%
“…Good agreement was achieved for heat transfer fluid temperature gain (ΔT) and collector thermal efficiency as shown in Table 2 and also in one of our previous investigations (Mwesigye et al, 2014a). …”
Section: Validation Of Numerical Modelsmentioning
confidence: 51%
“…The fluid friction from the present study was validated with the friction factor correlations by Petukhov [66] given by Eq. (36) and a correlation from Mwesigye et al Present study Mwesigye et al [16] Gnielinski correlation [66] Present study Petukhov correlation [66] Mwesigye et al [16] Nu With the nanofluid models used, the Nusselt number correlations by Pak and Cho [67] and Mwesigye et al [37] in Eqs. (40) and (41) To have confidence in the receiver thermal model, the thermal efficiency values of this study were compared with those obtained in experimental investigations by Dudley et al [68] as shown in Fig.…”
Section: Validation Of Numerical Resultsmentioning
confidence: 99%
“…Similar to previous investigations [11,16,37], this profile was obtained using ray tracing implemented in SolTrace, an open source ray tracing software developed by the National Renewable Energy Laboratory (NREL) [58]. In the ray tracing procedure, the sun shape was taken as Gaussian distribution with ζ sun = 2.6 mrad [58], the maximum number of sun generated rays was set to 10 8 , and the desired number of ray intersections was set to 10 6 .…”
Section: Absorber Tube Heat Flux Profilementioning
confidence: 99%
See 2 more Smart Citations